2010
DOI: 10.2169/internalmedicine.49.3047
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Acylated Ghrelin Levels are Associated with the Development of Cardiovascular Disease in Hemodialysis Patients

Abstract: Background Ghrelin has a protective effect on endothelial cells. Endothelial cell dysfunction is associated with cardiovascular disease (CVD) and CVD remains the leading cause of morbidity in hemodialysis (HD) patients. Acylated ghrelin (A-Ghr) is the functional form of ghrelin, so we hypothesized that A-Ghr is associated with the occurrence of CVD in HD patients. Methods We conducted a prospective cohort study in 412 HD patients. The cohort was sub-grouped into low and high A-Ghr groups according to the media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Further, the levels of acyl ghrelin were lowest in the severe SGA category of malnutrition and in patients with poor appetite. It has been reported that low acyl ghrelin is associated with poor nutritional status, loss of appetite (Oner-Iyidogan et al 2011) and CVD (Chou et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the levels of acyl ghrelin were lowest in the severe SGA category of malnutrition and in patients with poor appetite. It has been reported that low acyl ghrelin is associated with poor nutritional status, loss of appetite (Oner-Iyidogan et al 2011) and CVD (Chou et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In general, plasma ghrelin level increases after fasting and decreases after eating and plasma ghrelin level was found to associate with nutritional disorder in patients with advanced-stage cancer and anorexia nervosa[14]. A low ghrelin level increases the risk of cardiovascular mortality and morbidity in hemodialysis patients[15], and in recent clinical trials, administration of ghrelin improved appetite and food intake in dialysis patients[16,17]. The usefulness of monitoring plasma ghrelin at fixed intervals as a biomarker for mortality in hemodialysis patients has been proven[7].…”
Section: Introductionmentioning
confidence: 99%
“…We did not find significant associations of current H. pylori infection with the plasma ghrelin level. However, our observations might suggest that management practices, such as H. pylori eradication therapy, before the development/progression of atrophy is necessary to prevent the decrease of ghrelin level that is related with cardiovascular mortality and morbidity and with PEW in HD patients [6,7] . In addition, we demonstrated that because there was a positive correlation between PG I and ghrelin levels even in HD patients, ghrelin, PG I, and PG II levels, and PG I/II ratio might be useful markers for atrophy related with gastric cancer development and for nutrition status.…”
Section: Discussionmentioning
confidence: 90%
“…Administration of ghrelin is reported to improve problems in cachectic patients with congestive heart failure and chronic obstructive pulmonary disease [2] . However, although a low ghrelin level is a risk factor for cardiovascular mortality and morbidity in HD patients [6,7] , it is still unclear whether PEW status in HD patients significantly correlates with the plasma ghrelin level. In recent clinical trials, administration of ghrelin improved appetite and food intake in dialysis patients [8,9] .…”
mentioning
confidence: 99%